Secondary Frequency Control of Isolated Microgrid Based on LADRC - Kezhen Liu; Jing He; Zhao Luo; Xin Shen; Xinglin Liu; Tao Lu (IEEE Access, 2019)
The microgrid is considered to have bright prospects in the future for its advantages of high economic benefits and environmentally friendly and alleviate the antinomy for energy's supply and demand. Due to the introduction of renewable energy such as wind power into the microgrid, the intermittent, random, and unpredictability of its output makes it difficult to control the frequency when the microgrid operates in the isolated islands. In order to reduce the frequency fluctuation, this paper proposes a secondary frequency control strategy for isolated microgrid based on the linear active disturbance rejection control (LADRC) technology. Extended state observer (ESO) is used to estimate the extended state online and compensate the disturbance estimation actively so that the disturbance can be eliminated quickly and the frequency stability can be maintained. In addition, considering the demand response, the influence of different demand response coefficients on frequency control is analyzed. By a series of trial declarations, the LADRC control strategy can effectively suppress the frequency oscillation, and after adding the demand responses, the response speed can be faster than the traditional frequency modulation, reflecting its better robustness and stability. The simulation based on the frequency response model of AC microgrid results shows the effectiveness of the proposed method.